The determinants of capital structure in Islamic firms: the case for Malaysia, Saudi Arabia and Pakistan - Pg Hj Johari, Dk Siti Nur Khoirunnisaa (2019)
The objective of this study is to add to the literature by investigating the factors that determine the capital structure in Islamic firms. For that reason this study is using a sample of 342 Shariah compliant firms with complete data from three of the top 20 countries with the highest muslim population which includes Pakistan, Malaysia and Saudi Arabia for the period 2013-2017. Random effect regression analysis was used to determine the interplay between independent variables and measures of leverage. The findings revealed that there is no significant difference on the determinant of capital structure in the three countries. The significant relationships between all leverage measures with profitability, liquidity and risks are consistent with certain theories of capital structure. All country specific variables appear to have significant influence on total debt. And lastly, it was observed that national culture variables also have impact on capital structure of Shariah compliant firms. These findings may serve as a guide for newly established companies in determining the factors that should be considered for their financing decisions. The study also recommends that further research should be done on a larger sample of more Shariah compliant firms from other countries.